NORMA OPERATOR PADA RUANG FUNGSI TERINTEGRAL DUNFORD - Solikhin Solikhin; Susilo Hariyanto; Y.D. Sumanto; Abdul Aziz (Journal of Fundamental Mathematics and Applications (JFMA), 2019)
We are discussed operator norms on spce of Dunford integral function. We show that for a function which Dunford integral, operator from dual space into space of Lebesgue integral  is a bounded linear operator. Furthermore, sets of all bounded linear operator is a linear space and it is a normed space by norm certain. Finally, the distance function generated by the norm is metrix space.